STUDY OF WASTEDUMP EROSION CONTROL AT COAL MINING (Case: Catchment Area SP-9C PT. Adaro Indonesia - Kalimantan Selatan) - IASHANIA (NIM : 22115023), YUNIDA
Wastedump area is an open area mine without revegetation which can cause high erosion. Rain and runoff cause erosion and the increase of sedimentation in the settling pond causes the capacity of the sediment pond to decrease. This research was conducted at PT Adaro Indonesia, located in the area of wastedump that is catchment area DTH SP 9C. This study aims to reduce the erosion and environmental burden, therefore, it is necessary to assess erosion control and determine the prediction of erosion rate in the conditions of active heap areas. The prediction of erosion rate is influenced by rainfall erosivity using equations developed by Bols, Utomo, Foster and Williams and analyzes the material properties found on embankment based on the development of USLE (Universal Soil Loss Equation) method. The actual erosion occurring in DTH SP 9C in 2015 amounted to 461,829 tons/year and in 2016 amounted to 742,759 tons/year. The amount of erosion transported by the water flow is obtained from the measurement of water quality (TSS) and rainfall so that the equation Y = 333,03 x + 554,49. There were a prediction result surface erosion loads that transport sediment material due to runoff through the approach of accumulated TSS expression of daily sediment discharge in 2015 amounted to 518,395 tons / year and 2016 of 752,244 tons / year. The prediction of erosion based on the USLE method with the criteria approaching actual erosion is using the Bols equation of 2015 with (K = 0,25) of 1,222.37 ton / ha / year and year 2016 with (K = 0,30) 1,788,91 ton / ha / year. Based on the active condition of wastedump that occurred in 2015 and 2016, the erosion was very high so that erosion control efforts were needed, by applying the overburden to the design that had been made. Erosion control eforts for overburden such as; control erosion and water management (drainage system improvement, drop structure creation, sediment trap), and maintenance of a sediment pond (Safety pond).